In SilicoTools and Approaches for the Prediction of Functional and Structural Effects of Single-Nucleotide Polymorphisms on Proteins: An Expert Review - ÖZBEK SARICA, PEMRA (MARY ANN LIEBERT, INC, 2021)
Single-nucleotide polymorphisms (SNPs) are single-base variants that contribute to human biological variation and pathogenesis of many human diseases. Among all SNP types, nonsynonymous single-nucleotide polymorphisms (nsSNPs) can alter many structural, biochemical, and functional features of a protein such as folding characteristics, charge distribution, stability, dynamics, and interactions with other proteins/nucleotides. These modifications in the protein structure can lead nsSNPs to be closely associated with many multifactorial diseases such as cancer, diabetes, and neurodegenerative diseases. Predicting structural and functional effects of nsSNPs with experimental approaches can be time-consuming and costly; hence, computational prediction tools and algorithms are being widely and increasingly utilized in biology and medical research. This expert review examines thein silicotools and algorithms for the prediction of functional or structural effects of SNP variants, in addition to the description of the phenotypic effects of nsSNPs on protein structure, association between pathogenicity of variants, and functional or structural features of disease-associated variants. Finally, case studies investigating the functional and structural effects of nsSNPs on selected protein structures are highlighted. We conclude that creating a consistent workflow with a combination ofin silicoapproaches or tools should be considered to increase the performance, accuracy, and precision of the biological and clinical predictions madein silico.
Keywords: bioinformatics; SNP; proteomics; nonsynonymous single-nucleotide polymorphisms; in silicotools; human genetic variation; AMINO-ACID SUBSTITUTIONS; GENETIC-VARIATION; MOLECULAR-DYNAMICS; STABILITY CHANGES; WEB SERVER; MUTATIONS; DISEASE; DATABASE; VARIANTS; SEQUENCE